Wild boar management (Sus scrofa L.) in the Republic of Serbia - Lavadinović Vukan M.; Popović Zoran; Beuković Dejan M.; Cokoski Kristijan (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2020)
Wild Boar is an autochthonous big game species important for the domestic hunting sector. In the past decades this species is increasing in number across Europe, which influences the extent of crop damages and intensity of the human-wildlife conflict. In this study Wild Boar hunting management was analyzed both at the national and regional level. For that purpose data from management plans of 272 hunting grounds were used. Beside the management plans, this study includes a survey of 377 hunters. The results indicate that Wild Boar population abundance is increasing in the Republic of Serbia, partially because the planned and realized shooting are not harmonized. There are differences in hunting management between the regions of Vojvodina and Central Serbia. The survey has shown that among domestic hunters Wild Boar is a popular game species, especially due to the attractive way of hunting.